An Investigation about Education as Envisioned by Confucius and Its Implications for Contemporary Moral Education - Shaoan, Md Mirajur Rhaman; Jamil, Bushra; Musengamana, Irene; Mahamud, Akash; Chineta, Okoye Maureen; Arif, Muhammad; Namanyane, Tebatso; Akter, Jesmin (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study investigates Confucius' views on education and their rel-evance in the 4.0 era. Confucius is known as "the great model teach-er for centuries" for his dedication to education and his thoughts regarding its role, purpose, substance, and teaching techniques. Con-fucius founded Confucianism. Confucius felt education should be a right for everyone, not just the affluent. "No class difference in school" quickly transforms people's educational views. It makes formal schooling possible for most individuals. The idea of Confu-cius is innovative because people from all backgrounds desire jus-tice and equality in education. However, a synthesis of Confucius' education concepts based on past research adds to the literature on educational philosophy. Confucius's thoughts help people world-wide understand the incredible education ideas that have ever de-veloped in moral education. The results of this research can be guid-ed and affect modern educational authorities and policymakers.